Pengaruh Beban Kerja dan Konflik Peran Terhadap Burnout pada Mahasiswa Rekognisi Pembelajaran Lampau (RPL) Fakultas Ekonomi UKI Toraja - Srisetyawanie Bandaso; Ratih Pundissing (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This study aims to analyze the impact of workload and role conflict on burnout in students of the Recognitive Learning of Past (RPL) program of the University of UKI. Burnout, a condition of mental, emotional, and physical exhaustion, can have a significant impact on the academic performance of RPL students who have generally had work experience. Using a quantitative approach, the study involved a sample of 66 RPL students selected through cluster sampling. The data is collected using validated questionnaires and analyzed using the double linear regression method. The results of the t test showed that the workload had a significant influence on burnout with a t count value of 9,252 > 1,669 t tables. Similarly, the conflict of roles proved to have a significant impact on burnotes with the t count of 11,392 > 1,669 t tabels. These findings indicated that both independent variables had a strong positive influence upon burnout, with the role conflict showing a greater influence. The results of this study emphasize the importance of workload management and role conflict resolution in the context of RPL education to prevent burnout, improve student academic success and improve the quality of work.